Accommodation and Transformation of Islamic Educational Institutions in Indonesia: A Historical-Epistemological Analysis from the Classical Period to the Digital Era - Risnawati Risnawati; Idrus L (Journal of Contemporary Pedagogy and Learning Science, 2026)
This article examines the accommodation and transformation of Islamic educational institutions in Indonesia from the classical period to the digital era through a historical-epistemological perspective. Using a library research method and a descriptive-analytical approach, the study analyzes the historical development of Islamic educational institutions and the evolution of their epistemological foundations across different socio-political contexts. The findings indicate that Islamic education in Indonesia has historically evolved through continuous accommodation with local traditions, resulting in distinctive institutions such as mosques, surau, langgar, and pesantren, which integrated Sufi traditions, kuttab, and the indigenous guru-kula model. Classical Islamic education was constructed upon the complementary epistemological traditions of bayani, burhani, and irfani. During the colonial period, Dutch educational policies generated educational dualism and epistemological subordination, encouraging the establishment of madrasah as an adaptive institutional response. Following independence, institutional transformation continued through the formalization of madrasah and the transition from IAIN to UIN to promote epistemological integration between Islamic and modern sciences. In the digital era, Islamic educational institutions continue to accommodate technological change while confronting challenges related to scholarly authority, digital inequality, and knowledge integration. The study concludes that accommodation and transformation constitute the defining characteristics of Indonesian Islamic education, although achieving a genuinely integrated epistemological framework remains an ongoing intellectual challenge.